109 Effectiveness of Neuromuscular Electrical Stimulation for Children with Dysphagia: A Systematic Review. (29th October 2021) - Propp, Roni; Gill, Peter; Marcus, Sherna; Ren, Lily Yuxi; Cohen, Eyal; Friedman, Jeremy; Mahant, Sanjay
Abstract: Primary Subject area: Complex Care Background: Dysphagia is common in children with medical complexity and can result in undernutrition, respiratory complications and negatively impact child and caregiver quality of life; however, evidence on the effectiveness of treatments for dysphagia in children is limited. Neuromuscular electrical stimulation (NMES) is a novel proposed treatment for dysphagia where electrical current is applied to neck muscles using cutaneous electrodes during swallowing therapy. It is hypothesized that NMES improves dysphagia by strengthening swallowing muscles and/or enhancing sensory signals of the swallowing response. Objectives: To systematically review the evidence on the effectiveness of NMES for treatment of oropharyngeal dysphagia in children. Design/Methods: MEDLINE, EMBASE, PsycINFO, CINAHL, CENTRAL and Scopus databases were searched from inception to November 2020. Studies of children (18 years and younger) diagnosed with oropharyngeal dysphagia using NMES in the throat/neck region were included. Screening, data extraction, and risk of bias assessment followed PRISMA guidelines. Risk of bias was assessed using the Cochrane Collaboration's tool for RCTs and the Newcastle-Ottawa tool for observational studies. [Registration: PROSPERO CRD42019147353] Results: Of the 844 records screened, 26 were identified for full text review, and 8 studies were included (4 RCTs and 4 cohort studies). These studies represented 338 children, with a mean (or median) age below 7 years, including children with and without neurological impairments. In all studies, swallowing function as measured by imaging studies improved after NMES treatment; in the trials, the standardized mean difference ranged from 0.32 (95% CI -0.56, 1.20) to 1.18 (95% CI 0.40, 1.97) compared to control groups who received usual care without NMES. Seven of eight studies reported on the child's feeding ability, and, with one exception, there was improvement in feeding ability (Figure 1). Few studies reported on health status (N=1), child's quality of life (N=1), and adverse events and harms (N=1). No studies reported on the social impact on the child, impact on the caregiver, and the caregiver's quality of life. In most studies, outcome follow-up was limited to less than 6 months. Overall, the studies demonstrated moderate to high risk of bias. A pooled intervention effect and meta-analysis was not conducted due to clinical heterogeneity. Conclusion: NMES treatment may be beneficial in improving swallowing function for children with dysphagia, however, given the quality of the studies, inadequate outcome reporting, and short follow-up duration, additional well-designed RCTs are needed to establish its effectiveness.